Developing discerning consumers: an intervention to increase skepticism toward advertisements in 4- to 5-year-olds in the US. Issue 2 (3rd April 2018) - Stanley, Susie L.; Lawson, Chris A.
Abstract: This study examined whether an instructional intervention could increase skepticism toward advertisements in a sample of 4- to 5-year-olds ( N  = 44, M age = 4.46) from the US. Children in an intervention group observed toy commercials and had the opportunity to play with the advertised toy while they were told about advertisers' motives and the tactics they use to persuade consumers to want products. In a control condition, children were shown these same commercials and allowed to play with the advertised toy but were not instructed about the persuasive tactics used by advertisers. The intervention led to significantly higher rates of skepticism toward commercials more than a week after the training. These results have practical implications concerning ongoing debates about the efficacy of early media literacy interventions and theoretical implications regarding the mechanisms that underlie the development of skepticism.